BAYESIAN ANALYSIS OF MORTALITY RATES DUE TO CARDIOVASCULAR DISEASES IN SÃO PAULO STATE - SILVA, Diorgines Herculano da; ACHCAR, Jorge Alberto (Brazilian Journal of Biometrics, 2015)
In this paper, we describe and analyze different models for mortality from acute myocardial infarction for each municipality of São Paulo, for the years 2006 to 2010. To model the temporal count data, we consider the use of Bayesian procedures for estimate the relative risk as an efficient way to get the inferences of interest.